Biodiversity Afforestation Model - an Approach - Singh, Jarnail (Indian Forester, 1994)
In consonance to the changed objectives and goals of revised National Forest Policy 1988 and the emphasis given to biodiversity aspect of ecosystem management, it has become inevitable to modify our approach in tune with the changed perspectives. The afforestation programme should be so planned, formulated and implemented that each step bring us more close to the defined goal. To protect and maintain the biodiversity of forests and to integrate the biodiversity aspect with the afforestation programme is now a need of the time and the environment. Biodiversity Afforestation Model - An Approach is a step in this direction.